Cobern and Loving’s Card Exchange Revisited: Using Literacy Strategies to Support and Enhance Teacher Candidates’ Understanding of NOS - Allaire, Franklin (Innovations in Science Teacher Education, 2018)
The nature of science (NOS) has long been an essential part of science methods courses for elementary and secondary teachers. Consensus has grown among science educators and organizations that developing teacher candidate’s NOS knowledge should be one of the main objectives of science teaching and learning. Cobern and Loving’s (1998) Card Exchange is a method of introducing science teacher candidates to the NOS. Both elementary and secondary teacher candidates have enjoyed the activity and found it useful in addressing NOS - a topic they tend to avoid. However, the word usage and dense phrasing of NOS statements were an issue that caused the Card Exchange to less effective than intended. This article describes the integration of constructivist cross-curricular literacy strategies in the form of a NOS statement review based on Cobern and Loving’s Card Exchange statements. The use of literacy strategies transforms the Card Exchange into a more genuine, meaningful, student-centered activity to stimulate NOS discussions with teacher candidates.